2007
DOI: 10.1073/pnas.0706532104
|View full text |Cite
|
Sign up to set email alerts
|

Type VI secretion system translocates a phage tail spike-like protein into target cells where it cross-links actin

Abstract: Genes encoding type VI secretion systems (T6SS) are widely distributed in pathogenic Gram-negative bacterial species. In Vibrio cholerae, T6SS have been found to secrete three related proteins extracellularly, VgrG-1, VgrG-2, and VgrG-3. VgrG-1 can covalently cross-link actin in vitro, and this activity was used to demonstrate that V. cholerae can translocate VgrG-1 into macrophages by a T6SS-dependent mechanism. Protein structure search algorithms predict that VgrG-related proteins likely assemble into a trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
879
2
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 650 publications
(943 citation statements)
references
References 47 publications
17
879
2
10
Order By: Relevance
“…This is consistent with sizes of known effectors: 129‐kDa VgrG‐1, 113‐kDa VgrG‐3, or 155‐kDa pair VasX‐VasW (Dong et al , 2013; Joshi et al , 2017). Since 77‐kDa VgrG‐2 with no extension domain is required for T6SS assembly (Appendix Fig S3; Pukatzki et al , 2007), there is also enough space for effectors interacting with VgrGs, such as 72‐kDa TseL (Dong et al , 2013), in agreement with the model that many effectors bind to the VgrG/PAAR spike (Fig EV6; Shneider et al , 2013). However, the repertoire of secreted effectors is large (Durand et al , 2014; Alcoforado Diniz et al , 2015; Hachani et al , 2016), and therefore, it is likely that the overall shape of T6SS baseplate will vary between organisms.…”
Section: Discussionsupporting
confidence: 52%
“…This is consistent with sizes of known effectors: 129‐kDa VgrG‐1, 113‐kDa VgrG‐3, or 155‐kDa pair VasX‐VasW (Dong et al , 2013; Joshi et al , 2017). Since 77‐kDa VgrG‐2 with no extension domain is required for T6SS assembly (Appendix Fig S3; Pukatzki et al , 2007), there is also enough space for effectors interacting with VgrGs, such as 72‐kDa TseL (Dong et al , 2013), in agreement with the model that many effectors bind to the VgrG/PAAR spike (Fig EV6; Shneider et al , 2013). However, the repertoire of secreted effectors is large (Durand et al , 2014; Alcoforado Diniz et al , 2015; Hachani et al , 2016), and therefore, it is likely that the overall shape of T6SS baseplate will vary between organisms.…”
Section: Discussionsupporting
confidence: 52%
“…We previously showed that VgrG-1 in A. hydrophila ATCC 7966 T carries a C-terminal extension domain with ADPribosylation activity, and, through its T6SS, it targets host actin and promotes host cell apoptosis (Suarez et al, 2010a). VgrGs with C-terminal extension domains have been termed 'evolved VgrGs', and another such VgrG-1 with an actin cross-linking activity domain has been reported in Vibrio cholerae (Pukatzki et al, 2007). Interestingly, each effector has multiple copies, presumably paralogues of each other.…”
Section: Introductionmentioning
confidence: 99%
“…It may feature the effector function at the C-terminal domain. Such "evolved VgrGs" include Vibrio cholerae VgrG-1, with an actin cross-linking domain; Aeromonas hydrophila VgrG1, with an actin-ADP ribosylating VIP-2 domain; and V. cholerae VgrG-3, with glycoside hydrolase activity to target peptidoglycan (9,(25)(26)(27). Furthermore, VgrG may function as a carrier for effector delivery by binding directly with specific effectors carrying the proline-alanine-alanine-arginine (PAAR) domain (28,29).…”
mentioning
confidence: 99%